Production and effect of vermiwash and vermicompost on plant growth parameters of tomato (Lycopersicon esculentum Mill.) in Suriname - Vijantie R.R. Awadhpersad; Lydia Ori; Abdullah Adil Ansari (International Journal of Recycling of Organic Waste in Agriculture, 2021)
Purpose The purpose of this study was to to produce vermiwash and vermicompost using organic waste material and study its effect on the growth, development and yield of tomato plants(Lycopersicon esculentum Mill.) in field condition. Method The experiment was carried out in two phases: the production of vermicompost followed by vermiwash using Eisenia foetida earthworms and the cultivation of tomato plants using the same. In the first phase of production of vermicompost,  three types of organic waste (dry grass clippings, dry neem leaves and a combination of dry grass clippings and dry neem leaves) were utilized with three replications. The second phase consisted of a Randomized Block Design (RBD) with four treatments and three replications in the field condition. The treatments were control (C), vermicompost (V), vermiwash (W) and a combination of vermicompost and vermiwash (VW).ResultsThe results revealed that the vermicompost produced had a dark color, finely divided peat-like material, with desirable soil odor and a fine smooth texture and an adequate nutritional value, which was confirmed to have good quality. The vermiwash produced from the different vermicomposting bins was brownish colour liquid and had all the essential macro and micro-nutrients. The combination of vermicompost and vermiwash (0.05 kg + 0.05 l) significantly (p < 0.05) resulted in the highest yield followed by vermiwash (0.1 l) and vermicompost (0.1 kg).Conclusion The combination of vermicompost and vermiwash as a bio-fertilizer had a positive effect on the plant growth parameters and production of the tomato plants.